Digital Citizenship and Knowledge Management in Education: Strategic Pathways to Sustainable Development - Lomachinska, Irіna; Dobrodum, Olga; Ishchuk, Olena; Patlaichuk, Oksana; Stupak, Olga; Shnitser, Mariia; Salo, Hanna (European Journal of Sustainable Development, 2025)
The article examines the relationship between digital citizenship and knowledge management as key factors in sustainable development within the context of the digital transformation of education. Knowledge management in the digitalization of education refers to the systematic process of creating, preserving, disseminating, and effectively using information and educational resources through digital technologies to develop sustainable skills and competencies essential for societal progress. Digital citizenship encompasses the rights, responsibilities, and competencies required for active participation in the digital environment, ensuring engagement in public life through the use of digital educational technologies. It includes digital literacy, ethical online behavior, safe use of digital resources, and the ability to critically evaluate and create digital content. In conjunction with knowledge management, digital citizenship plays a pivotal role in the dissemination, storage, and application of information. Knowledge management enables the systematization of large data sets and the creation of digital educational platforms that enhance citizens’ awareness and participation in social processes. The digitalization of education provides the foundation for developing digital citizenship by fostering the necessary skills and competencies for effective interaction in the digital space. It promotes open access to knowledge, advances e-learning, personalizes educational processes, and prepares individuals for the efficient use of digital resources. At the same time, the authors emphasize the risks posed by the digital divide, cybersecurity threats, and the urgent need to cultivate digital competencies. Keywords: digital citizenship, identity, knowledge management, communication, sustainable development, knowledge society, civic education, digitalization of education, digital divide, digital competencies